QAZÍ MÁWLIK BEKMUXAMMED ULÍNÍǸ AǴARTÍWShÍLÍQ-JÁDIDShILIK XÍZMETLERI - Seytmuratov, Qalbay (SCIENCE and SOCIETY, 2026)
The article discusses the educational and innovative activities of the great son of the Karakalpak people, poet, teacher, storyteller, translator, and journalist Kazy Maulik Bekmukhammed oglu.